Relation between the continuum threshold and the Polyakov loop with the QCD deconfinement transition - Carlomagno, Juan Pablo (2019)
Using vector and axial-vector correlators within finite-energy sum rules with inputs from a chiral quark model, coupled to the Polyakov loop, with nonlocal vector interactions, we extend our previous work to confirm the equivalence between the continuum threshold s₀ and the trace of the Polyakov loop Φ as order parameters for the deconfinement transition at finite temperature T and quark chemical potential μ. The obtained results are in agreement with our initial conclusion, where we showed that s₀ (T,μ) and Φ (T,μ) provide the same information for the QCD deconfinement transition.